Deuteronomy and Human Rights - Braulik, Georg (Skrif en kerk, 1998)
If one compares the articles of the "Universal Declaration of Human Rights" dated December 10th, 1948, with the regulations of the book of Deuteronomy, one detects a surprising abundance of correspondences, or at least of similar tendencies, between them. As the social theorists of the seventeenth and eighteenth centuries, the architects of the catalogue of Human Rights, knew the Scripture very well. References to Deuteronomy are historically well probable and factually hardly coincidental. Deuteronomy rightly boasts about its social laws (4:8) that are unique in the Ancient Near East. The paper orientates itself to the short formula of Human Rights and at the same time to the normative basic character of each human right, as it is formulated in the first article of the declaration: "liberty", "equality", "fraternity". Each of these basic categories are concretised in terms of several Deuteronomic regulations and prove themselves to be central matters of concern within the YHWH religion. Finally, it is outlined how the connection between Deuteronomy and modem expressions of human rights might be explained, and further it is shown what actually makes up the peculiarity of biblical thinking on human rights.